PERLINDUNGAN HUKUM BAGI PEKERJA TAMBANG GALIAN C DALAM PERSPEKTIF PENGUPAHAN DAN KESEJAHTERAAN PEKERJA DI WILAYAH PROVINSI JAWA BARAT - Pepen Rustam; Martin Roestamy (Magister Hukum Sekolah Pascasarjana Unida, 2018)
Legal protection for Site C Miners is element that is implied in Article 27 of Undang-Undang Dasar 1945 where it is written that every citizen is equal in the eye of the law and have to obey the law. It also says that every citizen has rights for job and welfare in the name of humanity. The purposes of the research in Site C Mine in West Bandung Regency, Cianjur, Bogor Regency, West Java, are only to find out about Law Protection of Waging System and Welfare and whether the company of the Site C Mine follows the rule of minimum wage that is regulated in West Java region. The results of the research are for the miners of Site C Mine in 3 (three) regencies of West Java, the company already follows the rules and the Labor Law. However, according to research, there are workers who already work for 1 (one) year and get 12 (twelve) days of annual leave without cutting the wage. This thing is only applied to permanent workers, but not to outsource workers even though they already work for the company for years, and still be given welfare every year.